2020
DOI: 10.1080/1359866x.2020.1777529
|View full text |Cite
|
Sign up to set email alerts
|

Data use as the heart of data literacy: An exploration of pre-service teachers’ data literacy practices in a teaching performance assessment

Abstract: as the heart of data literacy: an exploration of pre-service teachers' data literacy practices in a teaching performance assessment. Asia-Pacific Journal of Teacher Education, . (In Press

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…Although there are increasing expectations for teachers to use data to make evidence‐based educational decision, the research on the implementation of teacher data literacies practice is still limited. Five reported the implementation of data literacies practice of in‐service teachers and pre‐service teachers (Boesdorfer et al, 2020; McDowall et al, 2020; Reeves, 2017; Reeves et al, 2016; Reynolds et al, 2019). For example, Boesdorfer et al (2020) conducted a nationwide questionnaire in the USA to examine secondary science teachers' perceptions of data‐driven instruction and data use.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are increasing expectations for teachers to use data to make evidence‐based educational decision, the research on the implementation of teacher data literacies practice is still limited. Five reported the implementation of data literacies practice of in‐service teachers and pre‐service teachers (Boesdorfer et al, 2020; McDowall et al, 2020; Reeves, 2017; Reeves et al, 2016; Reynolds et al, 2019). For example, Boesdorfer et al (2020) conducted a nationwide questionnaire in the USA to examine secondary science teachers' perceptions of data‐driven instruction and data use.…”
Section: Resultsmentioning
confidence: 99%
“…Reeves (2017) described that pre‐service elementary school teachers mostly used data to evaluate student learning and assign grades, evaluate and modify instructions, and plan for the next step during student teaching. McDowall et al (2020) also indicated that test data was the most common form in implementing pre‐service teacher data literacies practice in an Australian teacher education programme. There was little evidence for pre‐service teachers to use data from multiple sources to form a holistic understanding of student learning and inform their future instruction.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, some studies address data used in different contexts. McDowall et al (2021) examined pre-service teachers' uses of data to inform and evaluate their teaching practice and found that while some preservice teachers demonstrated many of the skills related to data use, others needed support. Although the context for assessing data literacy in this study (data from a natural phenomenon) is different from the context of the studies mentioned above (student data), similar results are pointed to.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Dutch Ministry of Education takes teachers' Data-driven decisionmaking ability as the main content of evaluating teachers' data literacy [45]. Australia regards teachers' Data-driven teaching decision-making ability as one of the core knowledge and skills of their performance assessment [46].…”
Section: ) Precision Teaching Decision-making and Teaching Interventionsmentioning
confidence: 99%